Integration of Educational Budget Planning and Public Relations Management in Enhancing Transparency of Financial Management in Modern Schools - Suuci Analismy; Taufik Hidayat; Tri Kuncoro Panji Murtanto; Tuti Isnani; Tamsik Udin (Jurnal Ar Ro'is Mandalika (Armada), 2026)
This study examines the integration of educational budget planning and public relations (PR) management as a strategic approach to improving transparency in school financial governance. The background highlights that while schools increasingly implement participatory and performance-based budgeting, transparency often remains procedural due to weak communication and stakeholder engagement. The research aims to analyze how the alignment of budget planning with PR functions can create transparent, accountable, and participatory financial management systems. Using a qualitative literature review method, data were collected from books, journal articles, policy documents, and reports from reputable academic sources such as UNESCO, OECD, and the World Bank. Thematic analysis was employed to synthesize concepts, policies, and best practices related to financial transparency in education. The results show that integrating budget planning and PR enhances institutional accountability, stakeholder trust, and effective communication of financial information. The study concludes that transparency becomes substantive and participatory when budgeting and communication processes are unified through strategic collaboration and ethical information management.